Implementation of Academic Supervision by the Principal in Strengthening Teacher Professionalism at Shine Alfalah Islamic Boarding School - Engla Guciano; Mia Audina Nst; Azizah Nur Azmi; Medina Septa Handayani; Salma Rosa; Akbar Saputra; Hamzah Nurqolbi Alharis; Azvi Rahmi; Serpuadi Zeky (Fakultas Agama Islam Universitas Muhammadiyah Sumatera Barat, 2026)
The implementation of academic supervision by the principal plays a crucial role in strengthening teacher professionalism and improving the quality of learning in schools. Academic supervision serves not only as a supervisory activity but also as a coaching, mentoring, and evaluation process to help teachers develop their professional competencies. However, in practice, various obstacles remain, such as teachers' poor ability to develop learning materials, a lack of creativity in using innovative learning methods, and minimal use of digital technology in the learning process. These conditions indicate that teacher professionalism has not developed optimally despite the implementation of academic supervision.This study used a qualitative approach with a descriptive approach. The research subjects consisted of the principal and teachers at the Shine Al-Falah Islamic Boarding School who were directly involved in implementing academic supervision. Data collection techniques were conducted through observation, interviews, and documentation. Data were analyzed using the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and conclusion drawing.The results indicate that academic supervision at the Shine Al-Falah Islamic Boarding School has been implemented through the planning, learning observation, learning material review, feedback provision, and evaluation stages. The principal has endeavored to implement supervision as a form of coaching to improve the quality of teacher learning. However, the implementation of academic supervision has not yet had an optimal impact on teacher professionalism due to several obstacles, such as low teacher motivation to develop competencies, a lack of pedagogical skills, the use of conventional learning methods, and weak follow-up on supervision results.Thus, academic supervision plays a crucial role in strengthening teacher professionalism, but its effectiveness is greatly influenced by teacher readiness and commitment to follow up on supervision results. Therefore, more collaborative, humanistic, and sustainable supervision is needed, accompanied by training, mentoring, monitoring, and motivation for teachers to achieve optimal professional development. Keywords: Academic Supervision, Principal, Teacher Professionalism, Learning Quality.